PENGARUH VARIASI PRODUK DAN LOKASI TERHADAP KEPUTUSAN PEMBELIAN PADA GLOW SUPERMARKET - Fadhl Gibran; Noor Hidayati; Taharuddin; Humaidi (Business Administration, FISIP ULM, 2025)
Fadhl Gibran, 2010412210009, 2024. The Influence of Product Variations and Locations on Purchase Decisions at Glow Supermarket, under the guidance of: Noor Hidayati. This study was conducted to find out and test the influence of partial and simultaneous Product and Location Variations on Purchase Decisions at Glow Supermarket. The research approach used is a quantitative method. The chosen research location is Glow Supermarket. Using the accidental sampling technique as a sampling technique, there were 100 consumers who were 18 years old and older and had shopped at Glow Supermarket more than 5 times who were selected to be reunited. Data collection using questionnaires and hypothesis testing using Multiple Linear Regression Test with SPSS tool version 25. The results of the study prove that Product and Location Variations have a significant effect partially and simultaneously on Purchase Decisions at Glow Supermarket.